Expression of Genes Encoding F(1)-ATPase Results in Uncoupling of Glycolysis from Biomass Production in Lactococcus lactis - Koebmann, Brian J. (American Society for Microbiology, 2002)
We studied how the introduction of an additional ATP-consuming reaction affects the metabolic fluxes in Lactococcus lactis. Genes encoding the hydrolytic part of the F(1) domain of the membrane-bound (F(1)F(0)) H(+)-ATPase were expressed from a range of synthetic constitutive promoters. Expression of the genes encoding F(1)-ATPase was found to decrease the intracellular energy level and resulted in a decrease in the growth rate. The yield of biomass also decreased, which showed that the incorporated F(1)-ATPase activity caused glycolysis to be uncoupled from biomass production. The increase in ATPase activity did not shift metabolism from homolactic to mixed-acid fermentation, which indicated that a low energy state is not the signal for such a change. The effect of uncoupled ATPase activity on the glycolytic flux depended on the growth conditions. The uncoupling stimulated the glycolytic flux threefold in nongrowing cells resuspended in buffer, but in steadily growing cells no increase in flux was observed. The latter result shows that glycolysis occurs close to its maximal capacity and indicates that control of the glycolytic flux under these conditions resides in the glycolytic reactions or in sugar transport.